ON CHARACTERIZATION OF MULTIWAVELET PACKETS ASSOCIATED WITH A DILATION MATRIX - Shah, F. A. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2015)
We provide a complete characterization of multiwavelet packets associated with dilation matrix based on results on affine and quasi-affine frames. Moreover, these characterizations are valid without any decay assumptions on the generators of the system.